Logic and Contemporary Linguistics - Pavilionis, Rolandas (Problemos, 1976)
The paper analyses certain problematic aspects of the interrelation between logic and linguistics. The author looks into the role of the formal methods in linguistic analysis and shows the function of the classical logical calculations in logically evaluating argumentation conveyed by natural language. It is shown that attempts to apply formal means more widely for evaluation of argumentation and its semantic coherence, as is the case in generative semantics, meet with difficulties of theoretical ant methodological nature, resulting in the necessity of formalizing all kinds of contexts.